UCH-L1 and GFAP Serum Levels in Neonates with Hypoxic–Ischemic Encephalopathy: A Single Center Pilot Study - Douglas-Escobar, Martha V.; Heaton, Shelley C.; Bennett, Jeffrey; Young, Linda J.; Glushakova, Olena; Xu, Xiaohui; Barbeau, Daphna Yasova; Rossignol, Candice; Miller, Cindy; Old Crow, Alissa M.; Hayes, Ronald L.; Weiss, Michael D. (Frontiers in Neurology, 2014)
Objective - We examined two potential biomarkers of brain damage in HIE neonates: glial fibrillary acidic protein (GFAP; a marker of gliosis) and ubiquitin C-terminal hydrolase L1 (UCH-L1; a marker of neuronal injury). We hypothesized the biomarkers would be measurable in cord blood of healthy neonates and could serve as a normative reference for brain injury in HIE infants. Further, we hypothesized that serum samples of HIE neonates would have higher levels and would correlate with brain damage on MRI and later developmental outcomes. Study Design - Serum UCH-L1 and GFAP concentrations from HIE neonates (n=16) were compared with controls (n=11). Pearson correlation coefficients and a mixed model design examined the relationship between biomarker concentrations of HIE neonates and brain damage (MRI) and developmental outcomes (Bayley-III). Result – Both biomarkers were detected in cord blood from control subjects. UCH-L1 concentrations were higher in HIE neonates (p<0.001) and associated with cortical injury (p<0.055) and later motor and cognitive developmental outcomes (p<0.05). The temporal change in GFAP concentrations from birth to 96 hours of age predicted motor developmental outcomes (p<0.05) and injury to the basal ganglia and white matter. Conclusion – UCH-L1 concentrations correlated with cortical injury and developmental delays and GFAP concentrations correlated with basal ganglia and white matter injury and motor delay in HIE affected patients. Researchers should continue to explore UCH-L1 and GFAP as promising serum biomarkers of brain damage and predictors of neurodevelopmental outcomes in neonates with HIE.